The Practicality and Effectivity of Audiovisual Media Usage in Increasing Learning Output of Drawing Polygon - Adisasongko, Nur; Khumaedi, Muhammad; Sutopo, Yeri (Universitas Negeri Semarang, 2021)
This research aimed to analyze the practicality and effectivity level of audio-visual usage in drawing polygon that developed by using Microsoft PowerPoint application and tested in state vocational (SMK N) 2 Kudus. The present research included research and development with applied ADDIE. The product was validated by media and material experts. The result of validation stated that the developed media in this research was valid and reliable based on the Content Validity Ratio, Content Validity Index, and Percent of Agreement. The product was practical with Ke= 0,93, and it was higher than the practical standard (0,90). This result was strengthened from the scalability test (Ks= 0,60), and the product achieved Ks=0,70 of the scalability. This result was higher than the required standard (Ks= 0,60). In the N-Gain score, the product got 71,34% or quite effective. The F count achieved 0,192 with Sig. (2-tailed) 0.000 0.05. This test showed a difference in average scores between the experiment and control class.